2017
DOI: 10.1155/2017/9548612
|View full text |Cite
|
Sign up to set email alerts
|

Association between VEGF Gene Polymorphisms and In-Stent Restenosis after Coronary Intervention Treated with Bare Metal Stent

Abstract: Background. In-stent restenosis (ISR) is the gradual narrowing of the vessel lumen after coronary stent implantation due to the increase in vascular smooth muscle cell proliferation. Vascular endothelial growth factor (VEGF) protein plays an important role in this process. Our aim was to analyze the association of single nucleotide polymorphisms of the VEGF gene (rs2010963 and rs6999447) with the occurrence of ISR after coronary artery bare metal stent (BMS) implantation. Methods. 205 patients with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
4
0
3
Order By: Relevance
“…In human studies, it was found that, following a decrease in NF-kB/p65 translocation, the expression of VCAM-1, E-selectin, and endothelial cell activation also diminished dramatically. Therefore, a reduced NF-kB/p65 pathway can be one of the valuable therapeutic targets to prevent the progression of ISR [104]. Studies show that among the various risk factors contributing to ISR, the role of genetics is very prominent.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, it was found that, following a decrease in NF-kB/p65 translocation, the expression of VCAM-1, E-selectin, and endothelial cell activation also diminished dramatically. Therefore, a reduced NF-kB/p65 pathway can be one of the valuable therapeutic targets to prevent the progression of ISR [104]. Studies show that among the various risk factors contributing to ISR, the role of genetics is very prominent.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we did not find any relationship between VEGFA rs699947 and the risk of binary ISR [ 10 ]. Moreover, Bagyura et al who analyzed the relationship between VEGFA polymorphisms and the risk of ISR in patients who underwent PCI with BMS implantation reported that rs699947 polymorphism is associated with neither the risk of diffuse nor focal ISR [ 50 ]. Our current analysis shows for the first time that the rs699947 A/A genotype is associated with a higher TLR risk.…”
Section: Discussionmentioning
confidence: 99%
“…Вони показали, що втрата просвіту була значно вищою в пацієнтів з генотипом A/А поліморфізму rs699947 гена ВЭФР-A порівняно з генотипами A/C і C/C (p < 0,05) [37]. Z. Bagyura та співавтори аналізували асоціацію двох поліморфізмів rs699947 і rs2010963 гена ВЕФР-А та розвиток рестенозу після імплантації металевого стента [4]. У цьому дослідженні поліморфізм rs699947 не був пов'язаний з ризиком розвитку рестенозу стента, та навпаки, наявність варіацій у локусі rs2010963 мала прогностичне значення.…”
Section: роль внутрішньосудинних зображеньunclassified